IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN PROSES PEMBELAJARAN DAN HASIL BELAJAR SISWA KELAS IV SD NEGERI 012 KUALU KECAMATAN TAMBANG KABUPATEN KAMPAR (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aims to improve the learning process and learning outcomes IPS grade IV SDN 012 Kualu Kampar regency. This was indicated by 40.62% of the 32 students achieve mastery minimum criteria (KKM) of the test scores of students in grade IV SDN 012 Kualu Kampar District Mining District to the subject. On average students is 61.56 and KKM expressed by schools is 60 based on this issue is needed to carry out action research using cooperative learning model Think Pair Share (TPS) type. This study aims to determine whether the implementation of cooperative learning model Think Pair Share (TPS) type can improve students' learning process and learning outcomes of social science in grade IV SDN 012 Kualu Kampar district in 2014/2015 with 32 students. This research was conducted in two cycles. The first cycle consisted of three meetings with the daily tests and the first tournament, the second cycle consists of three meetings with the daily tests and the second Tournament. instruments to collect data in this study is teacher observation sheets, and test. By applying using cooperative learning model Think Pair Share (TPS) type can improve student learning outcomes. Percentage of completeness in the base score is 40.62% (average 61.56), and it turned into a 65.62% (average 68.43) in the first cycle and, 81.25% (mean 76.25 average) at the second cycle. Percentage 'teacher activity in the first cycle was 64.59%, and 87.5% in the second cycle. Then the percentage of student activity in the first cycle was 62.5% and 87.5% in the second cycle. From these data prove that imlementation cooperative learning model Think Pair Share (TPS) type can improve student learning and learning outcomes in grade IV SDN 012 Kualu Kampar regency. Keywords: Cooperative learningmodelThink PairShare (TPS), Learning Prosesand Learning Outcomes